Lutas, leis e livros: professores de história na história do ensino no Espírito Santo (1850 - 1950) - Pirola, André Luiz Bis (2013)
This study analyzed the history of teachers in the process of formation of the subject of History in the Brazilian state of Espírito Santo. To that end, we investigated the activities of teachers which culminated in the constitution of the knowings and doings of the teaching of History in secondary school a century before the creation of courses that would prepare teachers for that level of teaching. In that sense, we delimitated two moments: the first one, in the second half of the nineteenth century, refers to the officialization of the post of History teacher by means of offerings of public teaching jobs aimed at the teaching of a specific subject. In doing so, we went back to the second half of the eighteenth century, at the time of the institution of the so-called instruções pombalinas , i.e., set of norms, promulgated by the Portuguese statesman Marquis of Pombal, for the teaching of Latin grammar, a subject that conveyed historical contents. The second one, ranging from the end of the nineteenth to the beginning of the twentieth century, features the discussions and establishments related to the normatization of the teaching of History set forth by the public power of the Gymnasio Espírito-Santense, a renowned boys school of the time. Our analysis was grounded on a corpus constituted by official documents, newspapers of the time and History textbooks that comprised the foundations for the understanding of the actions of teachers in the process of formation of History as a subject. We based our work on Roger Chartier (1990, 2009) and André Chervel (1990; 2001) in order to build the categories Humanist Fraternities (Fraternidades Humanistas), Productive Liberties (Liberdades Produtivas) and Distinctive Equalities (Igualdades Distintivas), articulating them to those of Fights, Laws and Books. As a result, we concluded that the formation of the subject of History in the state of Espírito Santo was made from the actions of teachers located in different fraternities. Some of these, in a way, professed History under strong teleological conceptions which transposed a Sacred History to a Profane History; on the other hand, other fraternities, fighting against this transposition, professed a teaching of History that potentialized the action of individuals and conflicts that crossed the period examined. We postulated that this shock was the indelible mark of the fights, laws and books upon which History teachers built the subject of History in secondary education in Espírito Santo